If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(y + 3) = 15 Reorder the terms: 5(3 + y) = 15 (3 * 5 + y * 5) = 15 (15 + 5y) = 15 Add '-15' to each side of the equation. 15 + -15 + 5y = 15 + -15 Combine like terms: 15 + -15 = 0 0 + 5y = 15 + -15 5y = 15 + -15 Combine like terms: 15 + -15 = 0 5y = 0 Solving 5y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '5'. y = 0 Simplifying y = 0
| (-3/4)n=6 | | 8a+7=70+9 | | (2/3)x=(1/3)x+(-10) | | 21x+35=20 | | 2m+5m=49 | | 21x-35=-20 | | 4y+9=32+5 | | 3x^2=5x+1 | | x/1.46/=3.25 | | 11+10x=1000 | | 11+17x=1000 | | 3x+4=2014 | | 10y+1=21 | | 4+2x=25 | | 24=9x+18 | | 5b-1+3b+2 | | 2+1.5(z+4)=3.5z-6 | | 3ln(2x)+6=9 | | -6d=-12 | | -3z/8=9 | | r^4-50r^2-625=0 | | 8a-5=67 | | 2n/3=0 | | 2+2.5(z+2)=4.5z-1 | | (5m^3/n^3)^3 | | (5x+14)=x | | (5x+14)= | | 2y-12=0 | | (x+13)=(x+23) | | 3y+8=23 | | (3x+5)(x+7)=0 | | 4y+3=6 |